Estimating Purchasing Power Parities from Household Expenditure Data Using Complete Demand Systems with Application to Living Standards Comparison: India and Vietnam. (13th October 2013) - Majumder, Amita; Ray, Ranjan; Sinha, Kompal
<x xml:space="preserve">Abstract</x> This study departs from the previous literature on purchasing power parity (PPP) by proposing a demand system based methodology for calculating the PPP that takes account of consumer preferences and allows for the substitution effect of price changes. The methodology is used to calculate the PPP between the Indian Rupee and the Vietnamese Dong. The study allows for regional variation in preferences and price changes both inside the country and between countries. It proposes and applies a methodology for constructing prices from unit values after adjusting them for quality and demographic effects. The adjusted unit values are used as prices in the demand estimations, and the demand parameter estimates are used to calculate both spatial prices within each country and the PPP between the two countries within a consistent framework. The study illustrates the usefulness of preference consistent methods to calculate the PPP by applying the PPPs to compare living standards between India and Vietnam. The significance of the results follows from the fact that the levels of living comparisons are quite sensitive to the PPP used in converting the Rupee expenditure into Vietnamese Dong. The present results on food PPPs question the relevance of the PPPs from the ICP project in cross‐country welfare comparisons especially in a period of high food inflation.